A Qualitative Study On The Implementation Of Ta'līm Al-Muta'allim Values In Character Formation At Man 4 Jombang - Fitroh, Mayada Fatwatul; Sirojudin, Didin (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2025)
This research was conducted at Madrasah Aliyah Negeri 4 Denanyar Jombang with the aim of examining the implementation of learning the Book of Ta'lim Muta'alim in shaping student character. This research uses a qualitative approach with the type of field research. The research results show that learning implementation is carried out through three stages: planning, implementation, and evaluation. Learning is carried out using classical methods involving bandongan and sorogan techniques, where students not only receive the material but also actively play a role in explaining and discussing the material. Evaluation is carried out to measure students' understanding and their character development. Apart from that, this research also identifies factors that support and hinder the formation of student character through learning the book. Supporting factors include adequate infrastructure, teacher competency, and book matriculation programs, while inhibiting factors include differences in student backgrounds, limited use of technology, and limited learning time. The positive impacts felt by students include increased respect for teachers, discipline, and mutual respect between friends, which reflects the implementation of character values in everyday life